2016
DOI: 10.1111/anec.12335
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Atrial Fibrillation following Alcohol Septal Ablation for Hypertrophic Cardiomyopathy

Abstract: Despite relieving LVOT obstruction and improving mitral regurgitation severity via ASA, new-onset AF remained a common complication of hypertrophic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…During 10‐year follow‐up, the cumulative risk of AF was at the level of 43% in patients with obstruction and 18% in those without . Another study in patients undergoing alcohol septal ablation (ASA) revealed that those who developed AF had significantly lower values of LVOT gradient after ASA ( P ≤ 0.005) . In a recent study, Lu et al found that significant left ventricular outflow gradient was related to a combined endpoint, a part of which was new onset AF .…”
Section: Discussionmentioning
confidence: 99%
“…During 10‐year follow‐up, the cumulative risk of AF was at the level of 43% in patients with obstruction and 18% in those without . Another study in patients undergoing alcohol septal ablation (ASA) revealed that those who developed AF had significantly lower values of LVOT gradient after ASA ( P ≤ 0.005) . In a recent study, Lu et al found that significant left ventricular outflow gradient was related to a combined endpoint, a part of which was new onset AF .…”
Section: Discussionmentioning
confidence: 99%
“…Moss et al studied 132 patients with no history of AF. During follow up 10 patients (7.6%) developed AF with only two having permanent AF, those affected tended to be older but the NYHA class was the same as the AF free group 40 …”
Section: Complications Of Alcohol Septal Ablationmentioning
confidence: 94%
“…Despite therapeutic anticoagulation, one patient developed stroke. [32] Follow up Long-term follow up is vital in order to ascertain the effects of ASA in patients with drug refractory HOCM. Usual methods include yearly echocardiograms looking into LVEF, septal wall thickness, valvular function, LV systolic and diastolic function.…”
Section: Complications Of Alcohol Septal Ablationmentioning
confidence: 99%